Effectiveness of yoga therapy as an adjunct on mental health status, quality of life, and medication adherence among people living with HIV on antiretroviral therapy: A study protocol of a randomized controlled trial (ART YOGA) - Dhanlika Dhanlika; Partha Haldar; Neeraj Nischal; Naveet Wig; Shruti Singh; Udisha Singh; Rajesh Sagar; Bimal Kumar Das; Sanjay Ranjan; Gautam Sharma (PLoS ONE, 2026)
Introduction Human Immunodeficiency Virus, the retrovirus that causes Acquired Immune Deficiency Syndrome, is a major global public health threat. This chronic viral infection diminishes the immune system by attacking CD4 cells. The principal treatment is antiretroviral medication (ART), which significantly increases the life expectancy of HIV patients. However, ART does not address psychological issues, including depression, anxiety, and stress. Psychosocial factors are known to influence HIV disease progression through activation of stress-related biological pathways, including the hypothalamic–pituitary–adrenal (HPA) axis, inflammatory cytokine responses, and monoamine neurotransmitter dysregulation. Mind–body practices such as yoga may modulate these pathways by reducing physiological stress, improving emotional regulation, and enhancing overall well-being. The current trial aims to assess the effectiveness of yoga as an adjunct therapy on psychological parameters (depression, anxiety, and stress), quality of life, and medication adherence of people living with HIV on antiretroviral therapy at a tertiary care hospital in AIIMS, New Delhi, India. Materials and methods This study is a two-arm, parallel-group, open-label, blinded-endpoint, single-center, randomized controlled trial investigating the effects of a yoga therapy as an adjunct therapy in people living with HIV (PLHIV). Participants (n = 192) will be randomized to either 12 weeks of a Yoga therapy program (n = 96) or an Active control group, i.e., a prescribed brisk walk (n = 96). Both groups will receive standard treatment. The primary outcome is anxiety and depression scores (HADS-A and HADS-D), and the secondary outcomes are Stress (PSS), quality of life (WHOQOL-HIV BREF and SF-36 QoL), and medication adherence. Discussion The findings of this RCT will help shed light on yoga intervention to address the psychosocial dimensions of HIV. If shown to be effective, yoga as an adjunct intervention may promote a transition in HIV care from a predominantly biomedical framework to a holistic, patient-centered approach encompassing mental health and overall well-being. The study is approved by Institute Research Board Ethics (AIIMSA2969/03.01.2025, RP-46/25, OP-16/02.05.25, OP-18/05.12.2025) and is registered at Clinicaltrials.gov (CTRI/2025/03/081645). CTRI Link- https://www.ctri.nic.in/Clinicaltrials/pmaindet2.php?EncHid=MTIyNjUx&Enc=&userName=HIV,%20Yoga